Individual perceptions of community resilience following the 2011 Joplin tornado. (26th April 2017) - Houston, J. Brian; Spialek, Matthew L.; First, Jennifer; Stevens, Jordan; First, Nathan L.
Abstract : Approximately 6–7 months after the deadliest tornado in the United States since 1947, we conducted a RDD telephone survey of Joplin residents ( N  =   380) to examine perceptions of community resilience (CR). We found that participants had positive perceptions of the resilience of their community after this major disaster. Older participants were more likely to perceive the community to be resilient than younger participants. More tornado experience was related to lower perceptions of CR. More use of traditional media (television and newspapers) for tornado information and more conversation with friends, family and neighbours about the tornado was associated with higher CR perceptions. Overall, mediated and interpersonal communication processes appear important for fostering CR following a major disaster.